25.7k views
5 votes
Please help ASAP 25 pts

Please help ASAP 25 pts-example-1

1 Answer

3 votes

Answer:

y = -4(x+2)^2 +2

Explanation:

y = -4x^2 -16x-14

Factor out a negative -4 out of the first two terms

y = -4(x^2 +4x) -14

We will complete the square

(b/2)^2 is what we need to add

(4/2)^2 =2^2 =4

Remember the -4 on the outside so when we add 4 on the inside we are really adding -4*4 = -16 so we need to do the opposite on the outside -(-16) and add 16

y = -4(x^2 +4x+4) -14 +16

Simplify inside the parenthesis

y = -4(x+2)^2 +2

User Quack
by
5.2k points